NAMA SAMARAN DALAM UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 3 TAHUN 2017 TENTANG SISTEM PERBUKUAN - Tomy Michael (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
In the consideration of the philosophical foundation of the Law of the Republic of Indonesia Number 3 of 2017 concerning the Bookkeeping System, it is stated that developing national civilization through the development and utilization of science, information and / or entertainment through books containing Indonesian national values ​​and identity is an effort to promote prosperity. general and intellectual life of the nation as mandated in the Preamble of the 1945 Constitution of the Republic of Indonesia. But in Article 3 letter g of the Republic of Indonesia Law Number 3 of 2017 concerning the Bookkeeping System, justice is only interpreted as carrying out a bookkeeping system to realize equal opportunities for all levels of society in accessing quality and inexpensive books. Of course justice will be biased when the phrase "pseudonym" is declared by the government. This is contrary to the application for the International Standard Book Number and copyright request with the type of book created by the Ministry of Law and Human Rights. When a pseudonym has been declared, a solution must be taken, namely to conduct a judicial review to the Constitutional Court to cancel the phrase "pseudonym". This is very important so that conflicts of norms do not emerge with other laws and regulations.